Comparison Study between Adipsin Levels in Sera of Iraqi Patients with Diabetes and Neuropathy - Layla Othman Farhan; Baydaa Ahmed Abed; AshganSlman Dawood (مجلة بغداد للعلوم, 2023)
The current study was designed to compare some of the vital markers in the sera of diabetic and neuropathy patients via estimating Adipsin, Fasting blood Glucose(FBG), Glycated(HbA1c) hemoglobin, Homeostasis Model Assessment Index (Homa IR ), Cholesterol, High density lipoprotein (HDL), Triglycerides (T.G), Low-density, and lipoprotein (LDL), Very Low Density Lipoprotein (VLDL), in sera of Iraqi patients with diabetes and neuropathy. A total  of ninety  subjects  were divided into three groups: group I (30 diabetic with neuropathy males) and group II (30 diabetic males without neuropathy), and 30 healthy sujects were employed as control group. The results showed a significant decline in Adipsin levels (p>0.05) in neuropathy, T2DM group with respect to the control group, while,  no changes were recorded within both diabetic patients groups .The serum insulin level dropped considerably  in neuropathy, T2DM group in a comparison with control group. The Adipsin ROC curve showed a clear cut-off value (4510.813, 3967.08) when calculated in neuropathy, T2DM respectively. The study concluded that Adipsin  is a diagnostic factor for T2DM with neuropathy